Fältstudie om kalciums betydelse för potatisens skalkvalitet och lagringsförmåga - Weigl, Maria (2022)
Peel quality of the potato tuber is becoming increasingly important in potato cultivation. Consumers primarily demand potatoes that have an even, smooth, and fine peel. Tubers that have different types of scabs or other stains are rejected. In addition, farmers get paid more at higher peel quality. The storage capacity is also positively affected by a high peel quality prior to storage. In recent years, calcium (Ca) has been increasingly discussed in connection with tuber quality, but most often regarding the inner quality of the tubers. Research on how and to what extent Ca affects diseases on the peel is lacking. However, due to the central role of Ca in the plant’s membranes and cell walls, Ca could potentially also affect the quality of the tuber peel. One hypothesis is that higher concentration of Ca in the soil and thus in the peel leads to an improved tuber peel quality, something that was tested in this work. In this field study, which was carried out on commercial farms in Småland and Östergötland counties in Sweden, the effect of the Ca concentration in the soil and in the peel on tuber peel quality of potatoes in freshly harvested and stored potatoes. A total of 22 fields were included in the study. In each field, three areas with varying concentrations of plant available Ca were selected to achieve a gradient across the field. In each area, samples of 2x15 kg of potato tubers were collected. Half of each sample was analysed ocularly immediately after harvesting, whereas the other half was stored for later analysis. The evaluated parameters were skin discolorations, black scurf, powdery scab, common scab, silver scurf and skin cracking and the results were presented as percentage of infected tubers. In addition, peel nutrient concentrations were determined. The results showed that a higher Ca concentration in the peel led to lower levels of peel discoloration in stored potatoes. The level of silver scurf after storage also decreased at higher levels of Ca in the peel. The opposite effect was noticed for black scurf in stored potatoes as higher Ca concentrations correlated with higher levels of black scurf. There was no correlation between the Ca content in the soil and the different analysed peel diseases. Soil Ca concentration in the field should according to recommendations be above 100 mg Ca/100 g soil to avoid Ca related quality defects on the tuber, and this assumption was also tested. The result did not agree with this recommendation, however, it turned out that the level of skin discoloration as well as the total amount of all skin diseases decreased as Ca-AL increased in the section below 100. In this study, the concentrations of other nutrients in the peel were also shown to correlate with skin quality. Positive correlations were found between manganese and phosphorus concentrations and the skin discoloration in freshly harvested tubers. In addition, there was a negative correlation between skin discolorations and the calcium-to-magnesium ratio and the calcium-to-potassium ratio, respectively. Furthermore, there was also a negative correlation between peel zinc concentration and the total amount of all skin diseases in stored potatoes. To minimize the risk of reduced potato peel quality, farmers need to focus more on Ca, especially when Ca-AL is below 100 mg Ca/100 g soil. The potential positive impact of zinc in stored potatoes should also be further investigated. In addition, there is a need to focus more on manganese, which is added regularly in today’s potato production, and which might have a negative impact on the peel quality. Keywords: calcium, cultivation, manganese, peel finish, potato, potato quality, zinc